Configurations of Organizational Effectiveness and Efficiency - Ostroff, Cheri; Schmitt, Neal (Academy of Management Journal, 1993)
This study examined the relationship between various characteristics of organizations?including resource inputs, context, rules and regulations, goals, climate, and informal systems?and the effectiveness and efficiency of organizations. Data were collected from 172 secondary schools. Discriminant analyses of the data with the organizations categorized along effectiveness and efficiency domains revealed that different sets or configurations of organizational characteristics were meaningfully related to the different organizational classifications.